Antibacterial Properties in Fermentate Extracts of Endophytic Fungus Derived from Marine Algae Caulerpa lentillifera Against Gastrointestinal Pathogenic Bacteria - Paliwengi, Andi Sinrang (Fakultas Farmasi, Universitas Muslim Indonesia, 2024)
Endophytic fungi, residing symbiotically within living plant tissues, are a promising source of novel bioactive compounds. These fungi are known to produce secondary metabolites with a wide range of biological activities, including antibacterial properties. This study explored the antibacterial potential of fermented extracts from endophytic fungi isolated from the marine alga Caulerpa lentillifera, a food source consumed by coastal communities and traditionally used for medicinal purposes. Thin-layer chromatography (TLC) bioautography was employed to identify extracts with activity against common gastrointestinal pathogenic bacteria, such as Escherichia coli, Shigella dysenteriae, and Salmonella typhi. Two endophytic fungal isolates displayed promising antibacterial activity against these pathogens. TLC analysis tentatively identified the presence of flavonoids and alkaloids, potentially responsible for the observed effects. This research sheds light on the pharmacological potential of endophytic fungi and their applications in combating bacterial infections.